2012
DOI: 10.1007/s11547-011-0765-7
|View full text |Cite
|
Sign up to set email alerts
|

Does weight loss predict accuracy of setup in head and neck cancer patients treated with Intensity-Modulated Radiation Therapy?

Abstract: Weight loss is not a good clinical parameters for predicting an increase of setup errors. Other clinical and/or anthropometrical features should be prospectively evaluated in order to assess the need for re-planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the baseline (BL) day of CT simulation we recorded: anxiety [18] and pain [1924], before starting the simulation procedure (more on the measurements scales below); patient’s weight and height [25, 26]; intent of radiation therapy; variable influencing patient positioning such as shoulders forced down, scoliosis or kyphosis; some patient and environment variables such as presence of mobile dental prosthesis, use of bite for locking of the jaw, tracheostomy, voluminous beard, voluminous hair, room temperature of the CT room and temperature of the water used for shaping the thermoplastic mask; type of standard neck supports used and the eventual addition of customized neck support; number of radiation therapy team members who worked together to shape the thermoplastic mask and temporary removal of the mask before the acquisition of CT simulation. On the first day of every week of treatment we measured the patient’s weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the baseline (BL) day of CT simulation we recorded: anxiety [18] and pain [1924], before starting the simulation procedure (more on the measurements scales below); patient’s weight and height [25, 26]; intent of radiation therapy; variable influencing patient positioning such as shoulders forced down, scoliosis or kyphosis; some patient and environment variables such as presence of mobile dental prosthesis, use of bite for locking of the jaw, tracheostomy, voluminous beard, voluminous hair, room temperature of the CT room and temperature of the water used for shaping the thermoplastic mask; type of standard neck supports used and the eventual addition of customized neck support; number of radiation therapy team members who worked together to shape the thermoplastic mask and temporary removal of the mask before the acquisition of CT simulation. On the first day of every week of treatment we measured the patient’s weight.…”
Section: Methodsmentioning
confidence: 99%
“…Pain was measured using the Numeric Pain Rating Scale, [1924] a numeric scale that describes the intensity of pain, ranging from 0 (no pain) to 10 (max value of pain); the measurement was performed directly by the patients themselves in the waiting rooms.…”
Section: Methodsmentioning
confidence: 99%
“…Two prior studies retrospectively looking at the effect of weight loss did not find a significant correlation between weight loss and set-up errors. 48,49 Another study, however, found a higher set-up shift with larger PTV requirements for patients with weight loss and laryngeal cancer. 7 In another study, the systematic errors were slightly higher in the lateral and antero-posterior direction in patients whose weight loss was >5%, but the required PTV margins for set-up error were within 5 mm.…”
Section: Discussionmentioning
confidence: 98%
“…The correlations between ΔBW and Δ(inter) were significant in several studies [23,24], although some studies reported contrasting results [25,26]. Hou et al [23] reported that patients with nasopharyngeal cancer with weight loss of >5% had significantly larger ΔAP(inter).…”
Section: Discussionmentioning
confidence: 99%